Seasonality, Tourist Attractions, Amenities, and Visit Intention: Insights from Bale Mangrove Ecotourism, Lombok - Muhammad Fatwa Zain; Ni Made Eka Mahadewi; Titien Damayanti (LP2M IAIN Palopo, 2026)
This study examines the effects of tourist attractions and amenities on visit intention and investigates the moderating role of seasonality in the context of Bale Mangrove Ecotourism, Lombok. Using a quantitative approach, data were collected from 160 domestic tourists and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that both tourist attractions and amenities have a positive and significant effect on visit intention, with amenities showing a stronger influence. This finding highlights the importance of functional facilities in supporting tourists’ confidence and willingness to visit nature-based destinations. However, seasonality does not significantly moderate the relationships between tourist attractions, amenities, and visit intention, suggesting that domestic tourists tend to adapt to seasonal conditions when making travel decisions. The proposed model demonstrates strong explanatory and predictive power, contributing to the application of the Theory of Planned Behavior in ecotourism contexts. Practically, the findings provide insights for destination managers to balance experiential attraction development with consistent amenity quality to enhance sustainable tourism growth.